Evaluation of the need to distinguish between white and black patients in predicting the combined mesiodistal crown width of canines and premolars Avaliação da necessidade de distinção entre pacientes brancos e negros quando da estimativa da largura mesiodistal combinada da coroa de caninos e pré-molares - Cabral Etenildo Dantas; Joanna Martins Novais Barbosa; Ludmila Galindo França de Oliveira (University of São Paulo, 2006)
The aim of the present study was to evaluate the need to distinguish between white and black patients when predicting the combined mesiodistal crown width of canines and premolars in Recife. A sample of 120 dental casts (60 from black and 60 from white patients) was selected from the archives of dental clinics in Recife. The mesiodistal crown width of the maxillary and mandibular canines and premolars and of the mandibular incisors was measured in these casts using a caliper with an accuracy of 0.02mm. The combined mesiodistal crown width of these teeth in the black patients was compared with that found in the white patients, and also with the estimated values obtained by regression equations based on the sample of white patients and on a large sample of a population from the same city. The study demonstrated that there were no significant differences between whites and blacks in the combined mesiodistal crown width of any of the three analyzed teeth groups and also revealed that such equations were statistically accurate in estimating the mesiodistal crown width of canines and premolars in blacks. It was concluded that there is no need for specific tables or equations regarding the patient's race in the analysis of mixed dentition in Recife. O objetivo do presente estudo foi avaliar a necessidade de distinção entre pacientes brancos e negros quando da estimativa da largura mesiodistal combinada da coroa de caninos e pré-molares em Recife. Uma amostra de 120 modelos de gesso (60 de negros e 60 de brancos) foi selecionada dos arquivos de clínicas do Recife. As larguras mesiodistais das coroas dos caninos e pré-molares superiores e inferiores e dos incisivos inferiores foram medidas nesses modelos, utilizando-se um paquímetro com precisão de 0,02mm. As larguras mesiodistais combinadas desses dentes nos pacientes negros foram comparadas com aquelas encontradas nos pacientes brancos; e comparadas com aquelas estimadas por equações de regressão elaboradas com base na amostra de pacientes brancos e com base em uma ampla amostra de recifenses. O estudo verificou não apenas a não diferença significativa entre brancos e negros na largura mesiodistal combinada de nenhum dos três grupos de dentes analisados, como também verificou que equações elaboradas com base na amostra de indivíduos brancos ou na amostra de recifenses foram estatisticamente precisas em estimar a largura de caninos e pré-molares dos negros. O estudo concluiu que não há necessidade de tabelas ou equações específicas segundo a raça do paciente para a análise de dentição mista em Recife.